Developing the Capacity of ESCWA Member Countries to Address the Water and Energy Nexus for Achieving Sustainable Development Goals - United Nations (United Nations, 2018)
This Publication discusses the resource efficiency related technologies and the RE technologies from the perspective of Technology Transfer. This publication also identifies the issues associated with water and energy considerations when pursuing the transfer of new technologies that have an impact on the water-energy nexus within the regional context. As a result, this publication aims to assist the Arab countries in the process of building the capacity for exchange and collaboration across industrial sectors and various other establishments based on a common language and a set of assessment tools for pursuing the TT associated with RE and resource efficiency at the operational level, such as during investment planning or the operation and maintenance of water and energy utilities, oil and gas operation, or irrigation schemes.